Construction of Elementary Schools in Galicia and the Kingdom of Poland in Magazines of the late 19th and Early 20th Centuries - Walasek, Stefania (Biuletyn Historii Wychowania, 2018)
Among the numerous pieces of information pertaining to the social life of the population of the Kingdom of Poland and Galicia a number of notes and articles about the necessity to undertake the construction of schools were published. The authors would frequently mention the outrageous conditions in which children were forced to study, the lack of flats for teachers, and the failure to follow the rules of hygiene in schools. It was argued that combating illiteracy could bring positive results by securing the proper conditions for raising and educating all school-age children. Discussions in the press covered examples of local initiatives aimed at building schools, as well as ways of making the local communities of villages and towns more active.